The Coal City Imprint · Walking Ideological and Political Education ——An Exploration of the Moral Education Path of Integrating Jixi Mining Spirit into Primary School Research Courses - Yubin Jia (Education Research on Study Tours and Practice, 2026)
At present, study tours in primary and secondary schools have become an important form of moral education. However, in practice, there are still problems such as "emphasizing travel over learning", "emphasizing activities over connotations", and "emphasizing forms over education". The study tours remain at the surface level of "extracurricular activities" and have not upgraded to the orientation of "hidden moral education courses", making it difficult for students to truly understand the spirit of their hometown and red culture. Based on this, this paper takes the coal city of Jixi as an example to explore the integration path of the mining spirit in the moral education courses of study tours in primary and secondary schools, hoping to promote students to understand the history of the coal city, inherit the spirit of miners, and cultivate a deep love for their hometown and country through diverse study tour activities.